Leigh Hunt, Sport, and the Cockney Controversy Revisited - Strachan, John (Romanticism and Victorianism on the Net, 2011)
This essay examines Leigh Hunt’s attitude towards sport, a subject about which he had mixed feelings. On the one hand Hunt strongly denounced violent and death-dealing sports such as boxing, shooting and angling, and on the other he idealised those pastimes which seemed to him to call back a lost world of ‘Merry Old England’: cricket, quarterstaff and bowls. Hunt saw sports as ethics-in-action; to him they offered moral lessons, some malign (the corrupting effects of pugilism) others benign (the healthy influence of the sports of the village green). The essay also examines how Hunt’s examination of sport was made in gendered terms of ‘manliness’ and ‘effeminacy’, and concludes by arguing that Blackwood’s attack on Hunt and the so-called ‘Cockney’ school might usefully be read in the context of the contemporary satirical tradition of the ‘Cockney sportsman’.